A contact-less interactive tool for exploring archaeological data - Frangeskides, Frangiskos; Papantoniou, Giorgos; Lanitis, Andreas (My University, 2008)
We describe a contact-less system that allows interactive information retrieval and exploration. In particular we focus our attention on the development of a contact-less interactive system that can be used for the exploration and visualization of artefacts with archeological interest, using a GIS-based system. The basis of our approach is a tracking algorithm that is able to track head movements of the user. Based on head motion it is possible to move a cursor and select different options, in order to enable data exploration and presentation. The work for this project is in progress. We are currently in the process of implementing an information retrieval system that allows users to retrieve and view information related to Cypriot archaeological artefacts. Although the primary scope of our work is to develop a system that can be used in museums, it is possible to use such systems in other environments such as airports, information kiosks and for general internet browsing. The only extra requirement for using our system is a standard web camera used for capturing images of the user. When compared with other systems currently is use in similar applications (i.e. systems using touch screens), the proposed system offers similar functionality at significantly reduced cost. The results of a preliminary experimental investigation, demonstrate the potential of using the proposed system in applications involving the dissemination of cultural heritage related information.
Keywords: Interactive environments; Usability; Interface design for CH Applications